Co-Indexation in Predicate Argument Structure: The Characteristics of Quechua Ku - Van de Kerke, Simon (Revue québécoise de linguistique)

(untitled) (Université du Québec à Montréal, 1991)
AbstractThe aim of this article is to give an account of the characteristics of the Quechua verbal affix ku. It addresses the question of whether constructions that are reputed to be cases of syntactic NP-movement in other languages can be analyzed in the same way in Quechua. It is claimed that Quechua does not allow the external position to remain without a theta-role in Predicate Argument Structure, in that way excluding syntactic NP-movement. The effect of ku can be described as: co-index an internal argument with the external position in the mapping from Lexical Conceptual Structure to Predicate Argument Structure. In that way the projection of verbs, that in other languages subcategorize for an empty external position, is licensed.